Analisis Pragmatik Imperatif Dalam Novel Pulang Karya Tere Liye - Ilmi, Nur (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The study was descriptive qualitative research. A novel of Pulang was a data source of the research; utterance which contained the forms of imperative pragmatics and the meaning of imperative pragmatics was the data. Data were collected by employing documentation, reading, and not-taking technique. Data analysis techniques were conducted through several steps, namely data reduction, data presentation, conclusion, and verification of the results of the study. The results of the study reveal that the forms of imperative pragmatics discovered in a novel of Pulang by Tere Liye were three forms, namely the form of imperative pragmatics of statement, question, and hope. The meaning of imperative pragmatics were thirteen meanings, namely imperative pragmatics of command, asking, request, insistence, persuasion, appeal, granting, solicitation, asking permission, permit, invite, hope, suggestion. Based on the findings of utterance in the forms of imperative pragmatics and the meaning of imperative pragmatic, the researcher discovered messages delivered by the writer both in the social message and religious message. One of the social messages discovered by the researcher was an attitude of respecting each other revealed through utterances with the meaning of imperative pragmatics of asking permission.